Knowledge and attitudes towards Zika virus among medical students in King Abdulaziz University, Jeddah, Saudi Arabia - Nahla K. Ibrahim; Rana H. Moshref; Leena H. Moshref; Jawaher B. Walid; Hadeel S. Alsati (Elsevier, 2018)
Zika Virus (ZIKV) and its associated consequences remain vital public health challenge of international concerns. The current study was done to assess knowledge and attitudes towards ZIKV and the factors associated with good knowledge among medical students in King Abdulaziz University, Jeddah. A cross-sectional study was conducted among 426 students. They were selected through multistage stratified random sample method, 2016. A validated, confidential, interviewing questionnaire contained 25 knowledge and 10 attitude items was used. Descriptive and inferential statistics were done.Results revealed that Facebook was the commonest source of ZIKV information. About half of the participants correctly identified mosquito bites and vertical route as ZIKV transmission modes. However, smaller percentages recognized the sexual and blood transmission modes. Calculations of knowledge score revealed that 77.5%, 15.0%, and 7.5% of the participants obtained poor, fair, and satisfactory scores, respectively. Age, educational year and attending ZIKV training were significantly associated with good knowledge (p < 0.05). Concerning attitudes, about half of the participants agreed that ZIKV could add new burden on healthcare system of the affected countries. Most of participants were interested in learning more about ZIKV, emerging diseases and travel epidemiology.In conclusion, medical students had limited knowledge about ZIKV, and good attitudes towards learning about it. Conduction of ZIKV educational programs, and development of courses about emerging disease epidemiology are required. Keywords: Emerging diseases, Zika virus, Medical students, Knowledge, Attitude